2020
DOI: 10.1108/yc-08-2020-1201
|View full text |Cite
|
Sign up to set email alerts
|

The e-learning persuasion through gamification: an elaboration likelihood model perspective

Abstract: Purpose The purpose of this theoretical paper is to introduce a conceptual model to investigate e-learning persuasion through gamification elements using the social psychology theory of elaboration likelihood model (ELM). Design/methodology/approach The author systematically reviewed several theoretical and empirical papers which applied the ELM in various settings. Based on the literature, the author identified six research prepositions which facilitate to investigate e-learning persuasion through gamificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 97 publications
(110 reference statements)
0
10
0
Order By: Relevance
“…We may build on our model by looking at other mediating or moderating factors that could change the hypothesized link. Employee motivating elements and performance factors gathered from digital gig working platforms may also be included in the extension technique (Finkin, 2016; Jayawardena, 2020).…”
Section: Future Research Perspectives Limitations and Conclusionmentioning
confidence: 99%
“…We may build on our model by looking at other mediating or moderating factors that could change the hypothesized link. Employee motivating elements and performance factors gathered from digital gig working platforms may also be included in the extension technique (Finkin, 2016; Jayawardena, 2020).…”
Section: Future Research Perspectives Limitations and Conclusionmentioning
confidence: 99%
“…When information receivers receive information, they will make a series of credibility judgments, which will affect the information adoption decision (Ho and Bodoff, 2014). This model is suitable for studying the dynamic interaction process between various sources, information, context variables and receivers, the Elaboration Likelihood Model provides an organizational framework for it, which is a dual process theory that leads to persuasion results through attitude formation and changing (Nirma, 2020). The model divides the core path and the edge path into two persuasion paths based on the individual's attitude and behavior toward the information (Petty et al, 1983).…”
Section: Application Study Of the Elaboration Likelihood Modelmentioning
confidence: 99%
“…Gamification has been trending in many fields of research, especially in e-learning, online shopping, and human resources (Jabagi et al, 2019;Jayawardena, 2020;Owens, Baker, Sumpter, & Cameron, 2016;Rich, Lepine, & Crawford, 2010). Gamification failures can lead to worker demotivation (Behl et al, 2022), and a significant challenge in formulating gamification schemes is that participation in the gig economy ecosystem relies on workers' continuity, with workers failing to live up to expectations causing customer dissatisfaction (Behl et al, 2022).…”
Section: The Role Played By Digital Gig Workers In Evaluating Engagem...mentioning
confidence: 99%
“…It can be observed that the application of game elements in work-related tasks enables the development of strong relationships among gig employers and employees (Hasija et al, 2020;Högberg et al, 2019). A gameful experience differs from gamification in that, while gamification explicates any extrinsic motivation by using game elements-like points, badges, leader boards, etc.-to enhance worker performance (De Troyer et al, 2020;Dubal, 2017), a gameful experience focuses on intrinsic motivations such as positive emotions, relationships, meanings, and accomplishment by implementing gameful designs (Jayawardena, 2020;Lepanjuuri et al, 2018). A gameful experience comprises a series of activities embedded in work through digital and computer interfaces, but in a non-game context (Banik & Padalkar, 2021).…”
Section: H3 Swift Trust Has a Positive Impact On The Task Performance...mentioning
confidence: 99%
See 1 more Smart Citation